1983
DOI: 10.3758/bf03196987
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition from semantically related primes: Evidence of a category-specific inhibition

Abstract: The phenomenon of inhibition from generating successive items within a category, reported by A. S. Brown (1981), was examined in two experiments. Subjects responded on target trials by either generating targets (e.g., generating BASS to B when it followed the category name FISH, Experiment 1) or reading them (reading BASS when it followed the category name FISH, Experiment 2). Prior to target trials, all subjects received priming trials consisting of either one or four exemplars from a single semantic category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(157 citation statements)
references
References 53 publications
13
142
2
Order By: Relevance
“…However, the evidence of inhibition from prior exposure to semantically related material is derived from a variety of methodologies, including episodic recognition (Neely, Schmidt, & Roediger, 1983;Roediger & Neely, 1982) and recall (Mueller & Watkins, 1977), alphanumeric matching (Neill, 1979), target generation (Blaxton & Neely, 1983;Brown, 1981), and category matching (under certain conditions; Rosch, 1975). A theoretical integration of that literature with the present data will not be attempted here.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the evidence of inhibition from prior exposure to semantically related material is derived from a variety of methodologies, including episodic recognition (Neely, Schmidt, & Roediger, 1983;Roediger & Neely, 1982) and recall (Mueller & Watkins, 1977), alphanumeric matching (Neill, 1979), target generation (Blaxton & Neely, 1983;Brown, 1981), and category matching (under certain conditions; Rosch, 1975). A theoretical integration of that literature with the present data will not be attempted here.…”
Section: Resultsmentioning
confidence: 83%
“…First, given that nonexemplars showed no effect of satiation in the category membership task, we might hypothesize that the effect of satiation may be limited to reducing the accessibility of (the meaning of) exemplars of the category. Subjects may covertly but actively retrieve many exemplars from the category in anticipation of an exemplar target (Blaxton & Neely, 1983). To sustain retrieval of new candidate target exemplars during the extended, 3Q-repetition period, items that had been retrieved initially might need to be inhibited, effectively increasing RT for these latter items.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, inhibition of competitors would be generated when retrieval is attempted, but not when a fact is only read or studied (cf. Blaxton & Neely, 1983;Storm, Bjork, & Bjork, 2006). Studying (but not retrieving) a fact, however, would be expected to increase its cue-target strength and produce interference.…”
Section: Stimuli and Designmentioning
confidence: 99%
“…For example, in Blaxton and Neely (1983), participants were slower to generate a category exemplar when they had previously generated several exemplars from the same category relative to when they had generated only one member from the category. Response time as a function of trial is similar to that observed in retrieval from episodic memory in free recall (e.g., Rohrer & Wixted, 1994), potentially leading to the conclusion that OI in episodic and semantic memory is comparable.…”
Section: Discussionmentioning
confidence: 99%